2017
DOI: 10.1111/rec.12649
|View full text |Cite
|
Sign up to set email alerts
|

Does restoration work? It depends on how we measure success

Abstract: The restoration of 4 partial stream barriers was evaluated in watersheds of Terra Nova National Park, Newfoundland, Canada from 2009 to 2011. Brook trout (n = 462) were tagged and tracked moving through our study sites using passive‐integrated transponder telemetry and the restoration actions were assessed using 3 different measures: passage success rates; the range of passable flows; and the availability of passable flows. We considered the observed results within a before‐after‐control‐impact (BACI) design t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…Our results provide strong evidence that simpler designs (e.g. After, BA and CI) often yield different inferences to BACI designs, as observed empirically by previous studies (França et al, ; Mahlum et al, ; Osenberg et al, ; Smokorowski & Randall, ). We also found that BA and CI designs were more prone to underestimation than overestimation (Figure b), which is consistent with results from França et al () that showed a CI design underestimated the impacts of logging relative to a BACI design.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our results provide strong evidence that simpler designs (e.g. After, BA and CI) often yield different inferences to BACI designs, as observed empirically by previous studies (França et al, ; Mahlum et al, ; Osenberg et al, ; Smokorowski & Randall, ). We also found that BA and CI designs were more prone to underestimation than overestimation (Figure b), which is consistent with results from França et al () that showed a CI design underestimated the impacts of logging relative to a BACI design.…”
Section: Discussionsupporting
confidence: 84%
“…The disparities between the robustness of study designs and their usage is concerning as many studies may be making misleading inferences about anthropogenic impacts. Some empirical comparisons of the consequences of using BACI, BA and CI designs have been undertaken (Osenberg et al, ; França et al, ; Mahlum et al, ; Smokorowski & Randall, ). However, we are yet to understand how inaccurate simpler designs are relative to complex ones, or the influence of sample size on these patterns (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Our results provide strong evidence that simpler study designs (e.g. BA and CI) often yield different effect sizes and inferences to BACI designs, as observed empirically by previous studies (Osenberg et al 2011;França et al 2016;Mahlum 2018). Therefore, studies using After, BA and CI designs seriously risk presenting misleading conclusions on the impact of threats and interventions.…”
Section: Discussionsupporting
confidence: 67%
“…The disparities between the robustness of study designs and their usage is problematic because this may mean we are making misleading inferences about anthropogenic impacts. Although some empirical comparisons of the consequences of using BACI, BA and CI designs have been undertaken (Osenberg et al 2011;França et al 2016;Mahlum 2018), we still do not understand how much less accurate simpler designs are than more complex ones, or the influence on accuracy of increasing sample size of different study designs. A quantitative comparison of the accuracy of different study designs and their sample size would help us better understand these issues.…”
Section: Introductionmentioning
confidence: 99%
“…An additional general linear model was conducted to analyze the effect of the measures on goby size in the littoral zone, with square root-transformed total lengths of bighead and round goby as response variables and section and survey as factors. Statistical significance of the effects of the respective measures on goby abundance or size are revealed by the interaction term section x survey (Mahlum et al 2018). The level of significance was set at 5%.…”
Section: Discussionmentioning
confidence: 99%